Ground improvement using PET bottle waste as a potential reinforcement material for granular columns: an experimental approach - Sobhee-Beetul, Laxmee (Department of Civil Engineering, 2019)
Out of the many ground improvement methods aimed at ameliorating the weak engineering properties of certain soils, granular columns are often preferred due to their cost effectiveness and environment friendliness. Despite their high usage in other countries, this technology remains rather unpopular in South Africa. Therefore, this study was undertaken to extend the associated knowledge of the granular column within the local context. In line with the need to develop environmentally sustainable construction technologies, the study incorporated Polyethylene Terephthalate (PET) bottle waste as a reinforcement material for these columns. Several laboratory experiments were conducted to improve the load carrying capacity and settlement characteristics of a local fine silt. A wet silt bed (prepared at optimum moisture content or liquid limit) was created within a steel cylindrical tank. An ordinary granular column (OGC) or reinforced granular column (RGC) was then installed within the tank and a compressive vertical load was applied to the prepared sample up to a settlement of 50 mm. Reinforcement for the columns was used in different forms and arrangements. The stresssettlement characteristics were electronically captured and subsequently analysed. Posttesting, the deformation of the column was physically modelled by vacuuming out the column material to create an empty opening. A prepared wet mix of plaster of Paris and sand was then poured into the empty hole until it was filled to the top. Once set, the casted column was removed from the tank and its circumference was measured at different intervals up along the length of the column. This process was repeated after each test and these measurements were later used for determining the respective maximum bulging. The study confirmed that the inclusion of granular columns generally improved load carrying capacity, as well as reduced settlement in weak soils such as fine silts. Also, certain conditions of reinforcing of the columns further improved their performances. From the results, it appeared that reinforcing a column with a concentration of 0.1 % of randomly mixed fibres, and installed in a base soil at liquid limit, produced the largest percentage improvement of 244 % in load carrying capacity. Furthermore, the diameter of maximum bulging was reasonably low and was measured as 144 mm, compared to 150 mm for an OGC which was tested under similar conditions. The outcome of this study considerably extended the understanding of the reinforcement of granular columns using PET bottle waste. Since the concept of reinforcing granular columns with waste is new, several areas were identified for future research to further increase knowledge pertaining to this ground improvement method.